Assisted coupled quintessence - Amendola, Luca; Barreiro, Tiago; Nunes, Nelson (Arxiv, 2014)
We study models of quintessence consisting of a number of scalar fields coupled to several dark matter components. In the case of exponential potentials the scaling solutions can be described in terms of a single field. The corresponding effective logarithmic slope and effective coupling can be written in a simple form in terms of the individual slopes and couplings of the original fields. We also investigate solutions where the scalar potential is negligible, in particular those leading to transient matter dominated solutions. Finally, we compute the evolution equations for the linear perturbations which will allow these models to be tested against current and future observational data.
Gesehen am 10.11.2017